Freezing effects in a hydropower dam core in Sweden - Knutsson, Sven; Jantzer, Isabel (Luleå tekniska universitet, Geoteknologi, 2007)
The hydropower embankment dam in Suorva, Sweden, is located in north of the Arctic Circle. The region is known for cold winters and severe wind conditions. The construction was completed in 1972 and has since then been exposed to a wide temperature range and low annual mean temperatures, leading to the presumption that the fine-grained frost susceptible moraine core of the embankment was exposed to cyclic freezing and thawing. The aim of this project was to find indications for freezing processes that affect the structure of the soil. The project included field investigations and a theoretical thermal analysis carried out with a commercial finite element program. Results from this analysis showed that the freezing plane advances to a maximum depth of 5 m from the top of the core. Hence, it may be possible that frost action affects the construction in its function as hydraulic barrier. Softening due to freeze/thaw can form initial soft part where internal erosion may be initiated thus causing weak points in the dam structure. Godkänd; 2007; 20090814 (svek)